Differential equations with boundary-value problems - Zill, Dennis G. 1940-; Zill, Dennis G. 1940- (Brooks/Cole, Cengage Learning, 2013)
"This proven and accessible book speaks to beginning engineering and math students through a wealth of pedagogical aids, including an abundance of examples, explanations, "Remarks" boxes, definitions, and group projects. Written in a straightforward, readable, and helpful style, the book provides a thorough treatment of boundary-value problems and partial differential equations."--Publisher's website.